Shakespeare and philosophy : lust, love, and law - Belliotti, Raymond A., 1948- (Value Inquiry Book Series, 2012)
This book is an interdisciplinary work that weaves literary interpretation, legal theory, and philosophical doctrine about sex and love into a coherent mosaic in the context of two of Shakespeare's plays: The Merchant of Venice and Measure for Measure . In the process, the work advances literary interpretations of the plays including character studies of some of the main protagonists. The aim is partly theoretical but mostly practical: to demonstrate what we can learn about living a robustly meaningful and significant human life by taking Shakespeare's work seriously from contemporary philosophical and legal vantage points. Shakespeare does not reveal a tightly defined moral system that he is trying to urge upon his audience. Instead, Shakespeare challenges his audience to struggle with moral complexity as they confront conflicting elements surrounding legal and moral issues presented in his work and within the souls of his characters. His issues and their conflicts are also ours. Much of Shakespeare's work consists of raising weighty questions inextricably connected to the human condition and inviting his audience to ponder possible answers. The philosophical lessons about living our lives meaningfully and significantly that we can derive from Shakespeare are simple yet powerful.